Powerful recombination centers resulting from reactions of hydrogen with carbon–oxygen defects in n‐type Czochralski‐grown silicon. Issue 8 (27th June 2017) - Vaqueiro‐Contreras, M.; Markevich, V. P.; Halsall, M. P.; Peaker, A. R.; Santos, P.; Coutinho, J.; Öberg, S.; Murin, L. I.; Falster, R.; Binns, J.; Monakhov, E. V.; Svensson, B. G.
Abstract : It has been acknowledged for over 50 years that treatments with hydrogen can improve silicon semiconductor devices. In recent years, these have been used to an advantage in silicon solar cells reducing the loss of photo‐generated carriers at the silicon surface or at the silicon interface with dielectrics. However, we have found that in some types of silicon the in‐diffusion of hydrogen can result in the formation of powerful recombination centers composed of carbon, oxygen, and hydrogen which reduce the carrier lifetime and ultimately the efficiency of solar cells made from such material. Abstract : Carbon and oxygen are ubiquitous impurities in Czochralski‐grown solar silicon. Here it is shown that the interactions of these impurities with hydrogen, introduced during processing, can produce powerful recombination centers. These centers are likely to have an important effect on the minority carrier lifetime and, in consequence, on the efficiency of solar cells produced from Czochralski silicon with higher than usual carbon content.